Effects of newly developed entrainment model for a thermal hydraulic system code (SPACE) based on breakup of large droplets in reflood. (1st September 2020) - Yoon, Seung Hyun; Kim, Kyung Doo; Heo, Jaeseok; You, Byung-Hyun; Ha, Kwiseok
Highlights: During reflood, a large droplet has been simply treated in conventional codes. We implement and verify breakup from large droplets for an Eulerian system. We suggest new method to calculate the entrainment from breakup of a large droplet. We assess the reflood experiments with the rod bundle and compare the results. For FLECHT-SEASET and RBHT, the results of the modified code for are generally improved. Abstract: The accurate prediction of the fuel rod temperature from a peak cladding temperature to quenching is required for a thermal–hydraulic system code in the reflood phase within a pressurized water reactor. Although conventional codes have well predicted the wall temperature trends, inaccuracies with the hydraulic parameter such as the steam flow rate still remains. To predict reasonable results that reflect an actual phenomenon, we implemented the breakup of a large droplet generated in an inverted slug flow. We suggested a new method to estimate the entrainment for an Eulerian system code (SPACE). The new method was successfully verified and compared to the analytic results. After the modification, we obtained improvements on the steam flow rate, the wall temperature, PCT times, and quenching times for FLECHT-SEASET. For RBHT, it showed mixed results with a faster decrease of the wall temperature, which implies the possibility of a transition for the reflood phenomena.